2017
DOI: 10.3390/antiox6030051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms behind Free Radical Scavengers Function against Oxidative Stress

Abstract: Accumulating evidence shows that oxidative stress is involved in a wide variety of human diseases: rheumatoid arthritis, Alzheimer’s disease, Parkinson’s disease, cancers, etc. Here, we discuss the significance of oxidative conditions in different disease, with the focus on neurodegenerative disease including Parkinson’s disease, which is mainly caused by oxidative stress. Reactive oxygen and nitrogen species (ROS and RNS, respectively), collectively known as RONS, are produced by cellular enzymes such as myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
140
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(147 citation statements)
references
References 124 publications
(140 reference statements)
3
140
0
4
Order By: Relevance
“…That is, increases in NADH and hypoxanthine during ischemia account for the principal mechanism of ROS production after ischemia/reperfusion by XOD in the kidney (36). GSH is an antioxidant whose level increases by oxidative stimuli, and it detoxifies ROS with the sulfhydryl group (37). Ischemia/reperfusion-induced H 2 O 2 is detoxified by GSH, preventing it from causing oxidative injury.…”
Section: And Supplemental Tables 2-4)mentioning
confidence: 99%
“…That is, increases in NADH and hypoxanthine during ischemia account for the principal mechanism of ROS production after ischemia/reperfusion by XOD in the kidney (36). GSH is an antioxidant whose level increases by oxidative stimuli, and it detoxifies ROS with the sulfhydryl group (37). Ischemia/reperfusion-induced H 2 O 2 is detoxified by GSH, preventing it from causing oxidative injury.…”
Section: And Supplemental Tables 2-4)mentioning
confidence: 99%
“…Enzymes that inactivate toxic protein modifications by acting as deglycating enzymes are obvious second line defence systems. For a long time they were elusive, until recent work demonstrated that proteins of the Hsp31 family, generally viewed as molecular chaperones (Natkanska et al ., ), and members of the DJ‐1 family, were in fact deglycases (Ahmadinejad et al ., ). Furthermore, they were involved in genetic diseases.…”
Section: The Taming Of Fire and Its Consequencesmentioning
confidence: 97%
“…One interesting but still poorly understood pathway is the activation of NADPH oxidase (NOX) which results in an increase in oxygen superoxide. 5,6 Oxygen superoxide is then converted to hydrogen peroxide (H 2 O 2 ) by superoxide dismutase (SOD). It has been shown that endogenous H 2 O 2 , arisen from insulin stimulation, can inactivate PTP1B, which in turns potentiates insulin signal transiently, 7,8 as illustrated in Figure 2.…”
Section: Insulin Signal Pathway and H 2 O 2 Formationmentioning
confidence: 99%